Evaluation of pancreatic steatosis prevalence and anthropometric measurements using non-contrast computed tomography - Koç, Ural; Taydaş, Onur (Turkish Journal of Gastroenterology, 2020)
Background/Aims: Pancreatic steatosis (PS) is a subject of current interest and its prevalence has been reported to range from 16.1% to 30.7% using various radiological methods. This study aimed to evaluate PS prevalence with non-contrast computed tomography (CT).Materials and Methods: The non-contrast CT scans taken in 2016 and 2017 in our hospital were retrospectively screened. A total of 637 cases (320 males, 317 females) were included in the study. CT number measurements were performed from three anatomic regions of the pancreas using regions of interest (ROI) of approximately 1 cm2. The cases with a <0.7 ratio of the pancreatic over splenic CT number were accepted as quantitatively steatosis-positive. Anthropometric evaluations were undertaken by determining various parameters defined on CT.Results: PS was determined visually in 30.6% of the males and 29% of the females, and quantitatively in 32.8% and 30.6%, respectively. A positive agreement was determined between the quantitative and visual evaluations of steatosis (Cohen’s kappa coefficient=0.587, p<0.001). Although PS was seen to be mostly diffuse, the tail region of the pancreas was determined to be the area with most steatosis.Conclusion: PS is usually overlooked in radiology practice but it has a clinical presentation with non-insignificant prevalence. Current radiological methods are adequate in the evaluation of PS. The determination of the cut-off values for various criteria on non-contrast CT can provide more objective evaluations.